Drama with deaf people in a remote environment: the teaching material Catálogo de Drama (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article presents the development of a teaching material about Process Drama for deaf people. The Catálogo de Drama is composed of content for the preparation and execution of five Process Drama in single sessions, initially proposed to be developed in a remote environment. The article presents the origin of the material, linked to practices carried out in a Theater final course work, highlighting the main references and delving into specificities of theatrical work with deaf people. The lack of accessible teaching material, aimed at a specific audience, is also addressed, together with a reflection on the importance of the study of Deaf Culture in theater teaching.
Keywords: theater; deafness; process drama; teaching material